The Correlation Between Students Motivation and Their Speaking Skill at MAN 2 Padang - Raflis Raflis; Yolanda Gustari (Jurnal Ilmiah Pendidikan Scholastic, 2019)
This research aims to see whether or not there is a positive correlation between students' motivation and speaking skills. The population of this research is students of class X man 2 Padang in the 2028/2019 school year. Total students of all are 315 students. In determining the sample, researchers used cluster sampling techniques by taking two normal and homogeneous classes. In this study the total sample was 59 students. In collecting data, researchers used questionnaires and documents. Questionnaire to see student motivation used by students in TALK and documents to measure students' Speaking comprehension. In analyzing data, researchers used the product moment formula. After analyzing the data, the researchers found the value of the cognitive strategy t-test was 0.32 with a significant level of 0.05. The results of the t-table are 0.256 with a significant level of 0.05 and degree of freedom (df = n-2). This means that the t-count is higher than the t-table (0.32> 0.256). This means that the t-test is higher than the t-table so the hypothesis in this study is accepted. Based on this research it can be concluded that motivation in speaking ability influences students' speaking comprehension.